Impacts of gas properties and transport mechanisms on the permeability of shale at pore and core scale - Tian, Z.; Wei, W.; Zhou, S.; Sun, C.; Rezaee, Reza; Cai, J. (2022)
In this work, new integrated permeability models for micro-nanopores and fractal shale matrixes are constructed by coupling different transport mechanisms, adsorption phenomenon, and real gas effect. The applicability of these proposed models is verified by mathematical models, molecular dynamics simulation results, and experimental data. The impacts of gas properties on gas transport at the pore scale and the contributions of different transport mechanisms on gas flow at pore and core scale are analyzed. The apparent permeability at pore scale and core scale decreases with increasing pressure. The bulk gas transport in micropores is strongly reduced because of the adsorption of methane molecules. The real gas effect enhances both transition diffusion and surface diffusion under high pressure at pore scale. However, the effect of the real gas effect on the slip flow permeability is negligible. At pore scale, surface diffusion, transition diffusion, and slip flow successively dominate the gas transport with increasing pore diameter under lower pressure. At core scale, the dominating transport mechanism under lower pressure is mainly under the control of pore size distribution and gas type. For larger pores and shale matrixes, the Darcy's law is still effective for describing the gas permeability under higher pressure.